First principles study of structural, electronic and magnetic properties of Mg1-xMnxTe alloys - N. A., Noor; Shaukat Ali, Prof. Dr.; W., Tahir; A., Shaukat; Ali Hussain, Reshak, Prof. Dr. (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/